Revision of the relationship between anther morphology and pollen sterility by cold stress at the booting stage in rice. (7th July 2021) - Yamamori, Koichi; Ogasawara, Kei; Ishiguro, Seiya; Koide, Yohei; Takamure, Itsuro; Fujino, Kaien; Sato, Yutaka; Kishima, Yuji
Abstract: Background and Aims: Cold stress in rice ( Oryza sativa ) plants at the reproductive stage prevents normal anther development and causes pollen sterility. Tapetum hypertrophy in anthers has been associated with pollen sterility in response to cold at the booting stage. Here, we re-examined whether the relationships between anther abnormality and pollen sterility caused by cold stress at the booting stage in rice can be explained by a monovalent factor such as tapetum hypertrophy. Methods: After exposing plants to a 4-d cold treatment at the booting stage, we collected and processed anthers for transverse sectioning immediately and at the flowering stage. We anatomically evaluated the effect of cold treatment on anther internal morphologies, pollen fertilities and pollen numbers in the 13 cultivars with various cold sensitivities. Key Results: We observed four types of morphological anther abnormalities at each stage. Pollen sterility was positively correlated with the frequency of undeveloped locules, but not with tapetum hypertrophy as commonly believed. In cold-sensitive cultivars grown at low temperatures, pollen sterility was more frequent than anther morphological abnormalities, and some lines showed remarkably high pollen sterility without any anther morphological alterations. Most morphological anomalies occurred only in specific areas within large and small locules. Anther length tended to shorten in response to cold treatment and was positively correlated with pollen number. One cultivar showed a considerably reduced pollen number, but fertile pollen grains under cold stress. We propose three possible relationships to explain anther structure and pollen sterility and reduction due to cold stress. Conclusions: The pollen sterility caused by cold stress at the booting stage was correlated with the frequency of entire locule-related abnormalities, which might represent a phenotypic consequence, but not a direct cause of pollen abortion. Multivalent factors might underlie the complicated relationships between anther abnormality and pollen sterility in rice.